If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + 2x(3) = 4x + 9 Reorder the terms for easier multiplication: 7 + 2 * 3x = 4x + 9 Multiply 2 * 3 7 + 6x = 4x + 9 Reorder the terms: 7 + 6x = 9 + 4x Solving 7 + 6x = 9 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 7 + 6x + -4x = 9 + 4x + -4x Combine like terms: 6x + -4x = 2x 7 + 2x = 9 + 4x + -4x Combine like terms: 4x + -4x = 0 7 + 2x = 9 + 0 7 + 2x = 9 Add '-7' to each side of the equation. 7 + -7 + 2x = 9 + -7 Combine like terms: 7 + -7 = 0 0 + 2x = 9 + -7 2x = 9 + -7 Combine like terms: 9 + -7 = 2 2x = 2 Divide each side by '2'. x = 1 Simplifying x = 1
| 2f+3=9a-10 | | (6x)7x= | | 4(t-6)+6t=5(2t+4)-8 | | 8+4n=-12 | | Y^2=6Y | | 5*19= | | 5x-19= | | 15+2n=9 | | 7-2(-5x-9)+2x=4(2x-1)+3(x+12) | | -6=24 | | 4-5n=11 | | 24x+27=-36x-6 | | 3y=-72 | | -0.5b+0.44444444444=0.57142857142 | | -6+2x=-4 | | 2y^2-6y+4=0 | | -(6y+2)-(5y-4)=1 | | 4x+13=-78-9x | | 18=7.5h | | 1x-7= | | a^2+3a=2 | | 1.2y=6.84 | | 8-x+5x-3-8x= | | -2x^2+8x+4=0 | | .5(3x+5)=1 | | 5x+4-3x+5+2x-9= | | 4x+10+14x+3=157 | | 6x-16y=8 | | 6g=-72 | | 3z^2+5z-2=0 | | 8x-3=3x+27 | | -9x+12+4(3x-3)=7(x-2)-4x+14 |